Measuring equity in public health financing across provinces in South Africa - Maake, Marumo (My University, 2021)
The post 1994 government in South Africa has been struggling over the years to address the socio-economic imbalances that existed during the apartheid period. In that period public health services were severely fragmented. While efforts were made over the years to address the inequalities, health indicators suggest that huge challenges still exist. Therefore, this research assesses whether the allocation of public health resources are equitably distributed, using expenditure as a proxy. The methodology used entailed the development of a needs-based formula to measure if the public health expenditure is allocated based population needs across provinces. The formula requires the weighting of the public sector population for its different need factors such as age and sex characteristics, burden of disease and socio-economic indicators such as deprivation indices. The findings of the research revealed that the distribution of public health resources are skewed towards certain provinces. This means that there is an inequitable distribution of health services across provinces and therefore the health allocations are not based on the needs of the population. Critical priority areas such as medicines, medical supplies and laboratory services are worst affected by the skewed distribution.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Management in Public Policy to the Faculty of Commerce, Law and Management, School of Governance, University of the Witwatersrand, Johannesburg, 2021
Keywords: Equity; Health financing; Expenditure; Public health financing; UCTD; SDG-3: Good health and well-being; SDG-8: Decent work and economic growth